CattleSavior: towards implementing an advanced external disease detection system through deep learning - Das, Rantu; Sinha, Yousuf; Sahid, Sohidul Haque; Kar, Dipta Dipayan; Shaheen, Shahidul Haque (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.